Nursing care for tachycardia patients undergoing radiofrequency ablation : A comparative study of 2 cases: การพยาบาลผู้ป่วยหัวใจเต้นผิดจังหวะที่ได้รับการรักษาด้วยการจี้ไฟฟ้าหัวใจ ด้วยคลื่นความถี่วิทยุ: กรณีศึกษา 2 ราย - kaewsankhum, Chariyapron (Journal of Nursing and Health Sciences Nakhon Phanom University, 2024)
Atrioventricular nodal reentrant tachycardia (AVNRT) is the most common form of paroxysmal supraventricular tachycardia. Currently, radiofrequency ablation is the treatment of choice for recurrent prevention. The aim of this study was to report the characteristics of patients with typical AVNRT who underwent radiofrequency ablation, recurrent rates, and complications of the procedure. Factors were analyzed to find potential predictors for AVNRT recurrence after radiofrequency ablation. In this case, two patients were at Sakon Nakhon Hospital between May and August 2023. This is intended to guide the development of standard nursing in cardiovascular clinics and hospitals that receive patients before and after a cardiac electrocardiogram comprehensively across all dimensions, both physical, mental, social, and spiritual, as well as being able to plan patient care at various stages effectively and maintain a good quality of life. Results: It was found that both patients were similar and different in various factors. Symptoms and signs before diagnosis the effects of treatment, discharge planning, and other. In terms of diagnosis Pre-Stage Nursing During and after the procedure, nursing diagnosis duration of hospital stay after providing nursing care using a holistic comprehensive nursing process, patients can be safely discharged home. Family and relatives are involved in the care of the patient and can continue to care for the patient when returning home.. In conclusion, this study will specifically focus on patient-exclusive information that has been examined. In this nursing process, nurses and medical personnel can apply it in accordance with the characteristics of the patient and the context of the agency. In order to improve the quality of care for patients with rapid heart attacks and other disorders.